2016
DOI: 10.1017/s1751731115002785
|View full text |Cite
|
Sign up to set email alerts
|

Updating the reference population to achieve constant genomic prediction reliability across generations

Abstract: The reliability of genomic breeding values (DGV) decays over generations. To keep the DGV reliability at a constant level, the reference population (RP) has to be continuously updated with animals from new generations. Updating RP may be challenging due to economic reasons, especially for novel traits involving expensive phenotyping. Therefore, the goal of this study was to investigate a minimal RP update size to keep the reliability at a constant level across generations. We used a simulated dataset resemblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Ly et al (2013) used real phenotypic and marker genotype data of cassava to suggest that training populations with close relatives to selection candidates attained higher prediction accuracy. Other simulation studies (Jannink, 2010; Iwata et al, 2011; Yabe et al, 2014; Pszczola and Calus, 2016) also suggested updating the prediction model during selection cycles, with the idea of using individuals close to the selection candidates as the training population. In animal breeding studies (Calus, 2010; Habier et al, 2010; Wolc et al, 2011), the decay of the prediction accuracy across generations was especially strong when the prediction methods depended on kinship information (or realized kinship calculated from use of markers).…”
Section: Discussionmentioning
confidence: 99%
“…Ly et al (2013) used real phenotypic and marker genotype data of cassava to suggest that training populations with close relatives to selection candidates attained higher prediction accuracy. Other simulation studies (Jannink, 2010; Iwata et al, 2011; Yabe et al, 2014; Pszczola and Calus, 2016) also suggested updating the prediction model during selection cycles, with the idea of using individuals close to the selection candidates as the training population. In animal breeding studies (Calus, 2010; Habier et al, 2010; Wolc et al, 2011), the decay of the prediction accuracy across generations was especially strong when the prediction methods depended on kinship information (or realized kinship calculated from use of markers).…”
Section: Discussionmentioning
confidence: 99%
“…Since the reliability of genomic prediction decreases as the genetic distance between reference population and selection candidates increases (Habier et al, 2010), reference populations need to be continuously updated to avoid a decline in relationships between the reference and the predicted populations and thus a decrease in accuracy of genomic prediction (Pryce et al, 2012a). Pszczola et al (2014) calculated a loss of accuracy per generation of 7% in a simulated reference population of 2000 cows in which no animals were added over the years. If the goal is to maintain the original level of accuracy, it is necessary to include new animals, whereby the selection of new individuals to enter the reference population is apparently more important than their actual quantity (Pszczola et al, 2014).…”
Section: Selection Of Informative Animalsmentioning
confidence: 99%
“…Pszczola et al (2014) calculated a loss of accuracy per generation of 7% in a simulated reference population of 2000 cows in which no animals were added over the years. If the goal is to maintain the original level of accuracy, it is necessary to include new animals, whereby the selection of new individuals to enter the reference population is apparently more important than their actual quantity (Pszczola et al, 2014). The opposite situation, removing data from former generations, is a practicable way to reduce computation requirements without loss in reliability.…”
Section: Selection Of Informative Animalsmentioning
confidence: 99%
“…In the present study, we showed that (i) reasonably high PA of genomic prediction can be their GEBV and to update the multi-environment prediction model for the next breeding cycle [67][68]. The process can be implemented in the framework of the pedigree-breeding of progeny of biparental crosses between members of the reference population of the breeding program that is used as the training population [36; 42].…”
Section: Implications For Breeding Rice For Drought Tolerancementioning
confidence: 99%